A csehszlovák-magyar lakosságcsere vallástörténeti vonatkozásai Csanád vármegyében - Miklós Péter (University of Szeged, Magyar Medievisztikai Kutatócsoport Szeged, 2017)
The ethnic proportions changed significantly in the central part of Csanád county, due to the Czechoslovakian-Hungarian population exchange. As a result of most of the Slovakian populace leaving, having inhabited the region since the 18th century, the majority of the Lutheran denomination gave way to the dominance of the Catholic Church. All these phenomena also resulted in ecclesiastic administrative difficulties. As my paper presents, these included the matter of church tax debts of the Lutheran Slovakian leaving, and organizational problems of the Catholic parish in Pitvaros. This study based on the documents from the Csongrád County Archives of the Hungarian National Archives (in Szeged and Makó). Aspects of religious history are discussed according to the documents of the Szeged-Csanád Episcopal Archives (Szeged) and the National Lutheran Archives (Budapest).